Investigation on novel synthesis approach for thinned planar arrays employing modified GA optimizer - Kumari Modi J.; Gangwar R.K.; Ashwin P.; Gangwar V.S.; Singh A.K.; Singh S.P. (My University, 2025)
In this article, a novel approach for the synthesis of thinned planar antenna (TPA) arrays is proposed which furnishes maximally reduced peak side lobe levels (PSLL). The proposed approach is effective not only for reduction in PSLL at boresight but also at pre-specified scan angles away from the boresight. A modified binary coded genetic algorithm is employed to determine best possible combination of 'ON' and 'OFF' antenna elements on array aperture corresponding to lowest possible PSLL. To evidence the capability of the proposed strategy, a 12×12-element antenna array is numerically contemplated. The results incurred at antenna boresight through the aimed strategy are equated with those of same sized arrays reported in literature. The array is further steered to the scan angles of 200 and 400 off the boresight and the results are compared with that obtained at antenna boresight. © 2018 IEEE.